PEMEROLEHAN MORFEM ANAK USIA 2 TAHUN SAMPAI 2 TAHUN 6 BULAN (THE MORPHEME ACQUISITION OF 2 UP TO 2 YEARS OLD AND A HALF KIDS) - Sri Mauliani Zulkifli (JURNAL BAHASA, SASTRA DAN PEMBELAJARANNYA, 2013)
AbstractThe Morpheme Acquisition of 2 Up to 2 Years Old and a Half Kids. The study waslimited in the scope of his language skills, especially in the morpheme children at age 2years to 2 years 6 months. In addition, some parents are still many do not keep up withher well-spoken language development in behavior and development. This study useda qualitative descriptive method. The study was done in order to determine the form ofmorphemes the child, the child form of words that are strung together in a sentence oneword to two word sentences at age 2 years to 2 years 6 months. The research data is amorpheme; free and bound. Techniques used in data collection is provocation, tapping,see the good involved, records and technical notes. The data generated is 150 childrenand 15 free morpheme bound morpheme. Obtained free morphemes more children thanthe bound morpheme. (1) being acquired morpheme children at age 2 years to 2 years6 months, a free morpheme and bound morpheme, (2) form morpheme obtained free ofchildren at age 2 years to 2 years 6 months, (3) form bound morpheme obtained bychildren at age 2 years to 2 years 6 months, and (4) morpheme form obtained from thespeech one word or two-word utterances. Children’s ability to obtain the child’s morphemeto be assembled into one-word utterances and the utterances of two words, even capableof using morpheme as child speech in everyday language.Keywords: free morphemes, bound morphemes, speech.AbstrakPemerolehan Morfem Anak Usia 2 Tahun sampai 2 Tahun 6 Bulan. Penelitian inidibatasi pada ruang lingkup keterampilan berbahasa anaknya khususnya pada morfemanak yang pada usia 2 tahun sampai 2 tahun 6 bulan. Selain itu, masih banyak sebagianorang tua tidak mengikuti perkembangan anaknya baik perkembangan bahasanyadalam bertutur dan perkembangan tingkah lakunya. Penelitian ini menggunakan metodedeskriptif kualitatif. Penelitian ini dilakukan dengan tujuan untuk mengetahui wujudmorfem anak, wujud kata yang dirangkai anak pada kalimat satu kata menjadi kalimatdua kata pada usia 2 tahun sampai 2 tahun 6 bulan. Data penelitian ini berupa morfem;bebas dan terikat. Teknik yang digunakan dalam pengumpulan data adalah pancingan,sadap, simak libat cakap, rekam dan teknik catat. Data yang dihasilkan anak adalah150 morfem bebas dan 15 morfem terikat. Morfem bebas lebih banyak diperoleh anakdaripada morfem terikat. (1) wujud morfem yang diperoleh anak pada usia 2 tahunsampai 2 tahun 6 bulan, berupa morfem bebas dan morfem terikat; (2) wujud morfembebas yang diperoleh anak pada usia 2 tahun sampai 2 tahun 6 bulan; (3) wujudmorfem terikat yang diperoleh anak pada usia 2 tahun sampai 2 tahun 6 bulan; dan(4) wujud morfem yang diperoleh dari ujaran satu kata atau ujaran dua kata.Kemampuan anak dalam memperoleh morfem bebas dan morfem terikat dari ujaran164satu kata dan ujaran dua kata, bahkan mampu menggunakan morfem sebagai ujarananak dalam bahasanya sehari-hari.Kata-kata kunci: morfem bebas, morfem terika